Biomass/coal steam co-gasification integrated with in-situ CO2 capture. (1st April 2015) - Masnadi, Mohammad S.; Grace, John R.; Bi, Xiaotao T.; Ellis, Naoko; Lim, C. Jim; Butler, James W.
Abstract: Addressing recent environmental regulations on fossil fuel power systems and both biomass fuel supply and coal greenhouse gas issues, biomass/coal co-gasification could provide a feasible transition solution for power plants. In the quest for an even more sustainable process, steam co-gasification of switchgrass and coal was integrated with in-situ CO2 capture, with limestone as the bed material and sorbent. Five gasification/carbonation (at <700 °C) and calcination (at >850 °C) cycles were performed in an atmospheric pilot scale bubbling fluidized bed reactor. Hydrogen production was enhanced significantly (∼22%) due to partial adsorption of CO2 by the CaO sorbent, shifting the gasification reactions forward, consistent with Le Châtelier's principle. Tar yield measurements showed that reducing the gasification temperature could be achieved without experiencing higher tar yield, indicating that the lime has a catalytic effect. The sorbent particles decayed and lost their calcium utilization efficiency in the course of cycling due to sintering. The co-existence of three types of solids (biomass, coal, lime) with different particle properties led to bed segregation. An equilibrium model was found to be useful in design of lime-enhanced gasification systems. Highlights: Biomass/coal steam co-gasification was integrated with in-situ CO2 capture. 5 gasification/carbonation (<700 °C) and calcination (>850 °C) cycles were performed. Lime-enhanced co-gasification enhanced hydrogen production significantly (∼22%). CaO decayed as an absorbent of CO2 due to sintering and some was lost by attrition. Equilibrium models are useful in design of lime-enhanced gasification systems.